UNVEILING PRETIBIAL MYXEDEMA: A CASE REPORT OF GRAVES’ DISEASE - Hashim, Uswaton Hasanah; Oon, Jen Hoong; Adam, Noor Lita (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Pretibial myxedema (PTM), a rare manifestation of Graves’ disease, holds importance as it constitutes a component of the classical triad associated with the condition. Historically observed in up to 5% of Graves’ disease patients, the incidence of pretibial myxedema has notably decreased, likely attributed to advancements in early diagnosis and prompt initiation of antithyroid therapy. We present a rare case of biopsy-proven pretibial myxedema in Graves’ disease. We reviewed case notes, investigation results, imaging studies and discussed prevalence based on published reports. CASE A 39-year-old Chinese male presented with significant weight loss, neck swelling and bilateral lower limb nodular skin lesions. Clinical examination revealed diffuse goiter and bilateral anterior shin swelling. Thyroid imaging showed features consistent with thyroiditis, while bilateral anterior shin lesions indicated pretibial myxedema. Biochemical analysis revealed elevated thyroid function tests and positive thyroid-stimulating hormone antibody levels (>40 IU/L). A skin biopsy confirmed dermal mucinosis consistent with myxedema. Antithyroid medications were initiated. The patient expressed willingness to undergo radioactive iodine treatment if remission is not achieved. CONCLUSION Global reported cases of PTM are scarce. In China, a retrospective study revealed a prevalence of 1.6% within thyroid disorders, notably 1.7% in thyrotoxicosis and 0.36% in other thyroid conditions. In Malaysia, reported cases of PTM are minimal. PTM typically coexists with ophthalmopathy, mainly affecting the pretibial region. Pathologically, it results from glycosaminoglycan accumulation triggered by circulating thyrotropin-receptor antibodies, akin to thyroid ophthalmopathy. In summary, PTM is a rare autoimmune manifestation of Graves’ disease, commonly associated with ophthalmopathy and localized to the pretibial region. Clinical diagnosis is typically straightforward, often obviating the need for biopsy, particularly when Graves’ disease is active.